The Future of Work and Social Media: The Reconfiguration of an Intersection - Bagger, Christoffer (2020)
ABSTRACT The nature of work at large is undergoing massive shifts (Standing, 2011), often facilitated by new digital technologies (Precarity Lab, 2019) while also being a great source of meaning in the lives of many people (Gregg, 2013). Therefore, it is vital to understand what role digital communication plays in shaping, maintaining, and directing the domain of work in the lives of individuals. Discussions of social media and work specifically have veered off into vastly different directions. Are social media always a type of unpaid exploitation (e.g. Andrejvic, 2011), are they only a distraction in the realm of “actual work” (e.g. North, 2010), or are they a venue of professional expressions (e.g. Johnson, 2017)? Giving a universal answer to these questions is impossible, as they each rely on very different conceptualisations of “social media” and even of “work”, and particularly of how these two subjects intersect. Understanding this may prove vital to how we perceive the coming future of work, where digital media – including ones not immediately related to work – may prove to play new and interesting roles. This article will map eight different conceptualisations of the intersection of “social media” and “work” as they implicitly appear in the existing research. These conceptualizations are informally inspired by 16 months of theoretical and empirical inquiries into the role of social media in working life. In the following these conceptualizations will be exemplified by references to existing peer-reviewed research, thus relying on what is commonly on what may be termed “certified knowledge” (Fernandez-Alles & Ramos Rodríguez, 2009). As I proceed through these different conceptualisations, I will emphasize what difference they make from the perspective of an individual, as opposed to groups, organisations or societies at large. This focus on the individuals’ perspective is not in order to situate individual agency as the definitive factor, but rather to convey a sense of how social media in and around working life may be perceived “from the bottom up”. I propose these conceptualisations as a useful tool for untangling both different individual experiences of how a given person may experience the intersection between their own social media use and their work, as well as a delineation of adjacent research interests around social media and work. Following my walkthrough of the conceptualisations, I will briefly discuss how they contrast, and particularly how the final conceptualisation of Social Media under Work provides new perspectives on the existing research. Following this, I will end on suggesting further avenues for research on the intersection of social media and working life. ABOUT THE AUTHOR/S Christoffer Bagger University of Copenhagen cbagger@hum.ku.dk Christoffer Bagger is a PhD fellow in Communication and IT at the University of Copenhagen. His research project approaches the concept of work-life intersection )(and balance) from the perspective of media and communication studies. Specifically, he looks at the recent proliferation of Enterprise Social Media in businesses. He is part of the research group "Personalizing the Professional", funded by the Independent research council of Denmark. New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).